(untitled) (Shahroud Journal of Medical Sciences, 2021)
Background: The effect of cosmetic surgery has always had doubts. In particular, these doubts are interpreted in the psychological field. Therefore, the study aimed to determine the effectiveness of cosmetic surgery on the feeling of inferiority, social identity, and psychological health of Cosmetic Surgery Applicant. Methods: The research method is pre-experimental (preliminary experiment) with a pre-test-post-test design with a six-month follow-up for one group. The statistical population of the study includes all patients referred to Pars clinic surgery center in Sari in 2020. The research population and by sampling method available to 15 of those who met the inclusion criteria and obtained the quorum from the research questionnaires as a sample of selection were. To collect information, the inferiority scale of Yao et al, the Social Identity Questionnaire (SIQ) of Imani, and the Psychological Health Questionnaire (PHQ) of Goldberg and Hillier were used. To analyze the research data, repeated measures analysis of variance with SPSS 18 software was used. Results: The results showed that cosmetic surgery affected the cognitive and social factors of cosmetic surgery applicants (Pvalue≤0.01). It has the greatest effect on psychological health, social identity, and inferiority, respectively. Conclusions: The results of this study show that cosmetic surgery can have a significant effect on reducing feelings of inferiority and social identity and greater psychological health, which as a treatment method is effective on psychological factors. Keywords: Cosmetic Surgery, Inferiority, Social Identity, Psychological Health